Decomposition of mediterranean leaf litters: A microcosm experiment investigating relationships between decomposition rates and litter quality - Cortez, J; Demard, J M; Bottner, P; Jocteur Monrozier, L (Soil Biology and Biochemistry, 1996)
he decomposition of four mediterranean species leaf litter (Sessile oak, Quercus petraea L.; Holm oak, Quercus ibex L.; Sweet chestnut, Castanea satiua Mill and beech, Fagus syluatica L.) was studied for 90 days under controlled conditions. Respiration and litter mass loss were measured in three types of microcosms: (1) Soil only; (2) Soil + l-y old litter and (3) Soil + l-y old litter + newly senescent litter (freshly fallen). Variations in chemical composition of the litters were determined before and after incubation by the pyroanalysis method. For newly senescent litters decomposition rates per day Kco, (calculated from CO, release) and K, (calculated from mass losses) fitted to the first order exponential decay decreased as follows: sessile oak (Kc,_,, = 0.0043; K, = 0.0049) > holm oak (Km, = 0.0031; K, = 0.0040) = beech (&o~ = 0.0030; K, = 0.0030) > sweet chestnut (Kc% = 0.0001; K,, = non- significant regression); For l-y old litters sweet chestnut (Ko,, = O.oo40, K, = 0.0065) > sessile oak (KEO, = 0.0035; K, = 0.0039) > beech (Kcc,, = 0.0030; K, = non-significant regression). All litters showed a reduction of lipid (mean loss 90.5%), hydrosoluble (mean loss, 54.2%), hemicellulose plus cellulose (mean loss, 40.6%) content and a relative increase of lignin content (mean gain, 34.4%). Among indicators of litter quality (C-to-N ratio, %N, %lignin, lignin-to-N ratio, HLQ), only some of them were correlated with litter decay. The best relationships were established between the decomposition rates (K,) and parameters integrating lignin contents (I = 0.997; n = 3; P < 0.01). The decomposition of l-y old litters fitted well with most of these parameters (0.999 < I < 0.997; n = 3; P < 0.01) in contrast to newly senescent litters
Keywords: Cellulose; decomposition; hemicellulose; leaf litter; Lignin; litter quality (voyant); mass loss; mineralization